Feasibility Analysis Of Palm Sugar Business (Case Study: Buluh Awar Village, Sibolangit District, Deli Serdang Regency) - Khairunnisa Rangkuti; Syawal Harahap; Sasmita Siregar; Tagor Hutauruk (JASc (Journal of Agribusiness Sciences), 2020)
This study aims to know the feasibility of processing business of Palm Sugar in Buluh Awar Village, Sibolangit district, Deli Serdang Regency. From the research results obtained the amount of palm sugar production of 278 kg with the price of Rp. 20,714,28 / Kg, then the amount of farmer's acceptance is Rp. 5,758,569.84 per month. The total cost incurred amounted to 3,270,777.16 in one month of production,industry revenue of Rp. 2.537.791,68. Sugar Palm processing business is feasible to be cultivated based on R / C and BEP criteria with R / C value of 1.79, BEP Price Rp. 11,585,53 BEP Production 13,99 Kg and BEP Revenue Rp. Rp 286.193,96/bulan